2013
DOI: 10.1007/s13197-013-1232-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salicylic acid and putrescine on storability, quality attributes and antioxidant activity of plum cv. ‘Santa Rosa’

Abstract: Plum fruit has a short shelf life with a rapid deterioration in quality after harvest. The primary goal of this study is to investigate and compare the effect of putrescine and salicylic acid on quality properties and antioxidant activity of plum during storage. The plum fruits (cv. 'Santa Rosa') were harvested at the mature ripe stage, and dipped in different concentrations of putrescine (1, 2, 3 and 4 mmol/L) and salicylic acid (1, 2, 3 and 4 mmol/L), as well as distilled water (control) for 5 min. The fruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 33 publications
9
37
0
Order By: Relevance
“…reported that the increase in SSC during fruit ripening was attributed to the increased activity of enzymes responsible for the hydrolysis of starch to soluble sugars. Similar results have been found in other fruits such as mango and plum . In this study, NO or ABA could lead to differential increases in SSC contents compared with the control.…”
Section: Discussionsupporting
confidence: 90%
“…reported that the increase in SSC during fruit ripening was attributed to the increased activity of enzymes responsible for the hydrolysis of starch to soluble sugars. Similar results have been found in other fruits such as mango and plum . In this study, NO or ABA could lead to differential increases in SSC contents compared with the control.…”
Section: Discussionsupporting
confidence: 90%
“…Titratable acidity and SSC contents are the prime contributors in determining the flavouring attributes of fruits (Raffo et al 2007). Effectiveness of salicylic acid in maintaining titratable acidity of plum fruits is supported by the earlier findings of Han and Li (1997); Srivastava and Dwivedi (2000) and Davarynejad et al 2015. The above authors showed that SA maintained higher acid content at the end of storage in apple and strawberry, respectively.…”
Section: Titratable Acidity and Juice Phsupporting
confidence: 70%
“…The observed effect of salicylates on delaying changes on quality parameters related to plum postharvest ripening could be attributed to their effect on delaying and decreasing ethylene production, given the climacteric behaviour of this plum cultivar , , . Similarly, it has been recently reported that postharvest SA treatment maintained quality parameters during storage in other plum cultivars, such as ‘Santa Rosa’, and ‘Satluj’ throughout a reduction in ethylene production. However, the present results show that preharvest treatment with salicylates not only maintained quality attributes during storage but was also effective in increasing them at harvest time.…”
Section: Resultsmentioning
confidence: 76%
“…A similar trend was observed for ascorbic acid, whereas concentrations of citric and fumaric acids increased from day 0 to day 40 of storage and no changes occurred in succinic acid concentration. The decrease in ascorbic acid during storage could be due to the conversion of dehydroascorbic to diketogulonic acid by oxidation due to ascorbate oxidase . However, it is important to note the effect of preharvest salicylate treatments in maintaining plum ascorbic acid levels during postharvest storage, due to its role as antioxidant with health beneficial effects in human beings .…”
Section: Resultsmentioning
confidence: 99%